2004
DOI: 10.1242/dev.00891
|View full text |Cite|
|
Sign up to set email alerts
|

Hedgehog and PI-3 kinase signaling converge on Nmyc1 to promote cell cycle progression in cerebellar neuronal precursors

Abstract: Neuronal precursor cells in the developing cerebellum require activity of the sonic hedgehog (Shh) and phosphoinositide-3-kinase (PI3K) pathways for growth and survival. Synergy between the Shh and PI3K signaling pathways are implicated in the cerebellar tumor medulloblastoma. Here, we describe a mechanism through which these disparate signaling pathways cooperate to promote proliferation of cerebellar granule neuron precursors. Shh signaling drives expression of mRNA encoding the Nmyc1 oncoprotein (previously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
202
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(214 citation statements)
references
References 55 publications
11
202
1
Order By: Relevance
“…Cultures grown in 6-well dishes were lysed with radioimmunoprecipitation assay (RIPA) buffer (150 mM NaCl, 1% NP- 40 Cell counting and statistical analysis. Cell counting was calculated as the percentage of positive cells (BrdU, HuC/D, etc.)…”
Section: Antibodies and Chemicals (I) Mouse Monoclonal Antibodiesmentioning
confidence: 99%
“…Cultures grown in 6-well dishes were lysed with radioimmunoprecipitation assay (RIPA) buffer (150 mM NaCl, 1% NP- 40 Cell counting and statistical analysis. Cell counting was calculated as the percentage of positive cells (BrdU, HuC/D, etc.)…”
Section: Antibodies and Chemicals (I) Mouse Monoclonal Antibodiesmentioning
confidence: 99%
“…HH ligands are well-known mitogens for neuronal precursors and lung mesenchyme, as well as for several other cell types (Pepicelli et al, 1998;Kenney et al, 2004). Moreover, given that reductions in Vegf-A expression and deletion of HIF1␣ result in defects in vascular development and deficits in tissue growth (Ferrara et al, 1996;Ryan et al, 1998;Schipani et al, 2001;Zelzer et al, 2004), one might expect that ventricular growth would be dependent on the development of a vascular supply.…”
Section: Probing the Role Of Cardiomyocyte Proliferation During Midgementioning
confidence: 99%
“…We have also shown that Hedgehog (HH) signaling acts downstream of FGF in the coronary vasculogenic pathway controlling the expression of VEGF ligands (Lavine et al, 2006). Given the extensive data highlighting the ability of both FGF and HH signaling to regulate multiple cellular processes, including cell proliferation, migration, differentiation, and vascular growth (Pepicelli et al, 1998;Kenney et al, 2004;Eswarakumar et al, 2005), it is unclear which component(s) of this FGF-dependent pathway is responsible for the coordinate regulation of myocardial growth and coronary vascular development.…”
Section: Introductionmentioning
confidence: 99%
“…Active GSK3b normally phosphorylates MYC at the threonine 58 (Thr58) residue, which facilitates the ubiquitinproteasome degradation of MYC protein. PI3K inhibition thus decreases MYC protein stability by releasing GSK3b from AKTmediated inactivation and therefore promoting MYC Thr58 phosphorylation and subsequent degradation (28)(29)(30)(31). Indeed, pharmacologic inhibition of the PI3K pathway is able to induce cell death in PTEN-deficient DLBCL cells as a result of MYC downregulation (32).…”
Section: Introductionmentioning
confidence: 99%